Risk of Children’s Dermal Exposure to Galaxolide through Personal Care Products - Patrícia Correia; Agostinho Cruz; Lúcia Santos; Arminda Alves (Cosmetics, 2015)
Galaxolide is the most used fragrance since the early 1990s, and it has been largely detected in environmental and biological matrices. This polycyclic musk is present in almost all of our daily products, so the risk of human exposure is substantial, as it had been proved by its detection in human tissues and fluids. Due to the lack of information about the concentrations found in consumer products, monitoring data is needed for exposure assessment purposes. Dermal contact, mostly by personal care products, seems to be the major route of human exposure to galaxolide, and, due to the immaturity of young children’s skin, exposure consequences can be worse in this population. The main objective of this study was to evaluate galaxolide levels in personal care products used by children of Oporto (Portugal), aged 0–5 years, and relate it with consumer habits. Consumer patterns were obtained through 250 questionnaires to caregivers of Oporto children. The 79 most used products were extracted by a dispersive solid phase extraction methodology known as QuEChERS and galaxolide was determined by High Performance Liquid Chromatography (HPLC) with fluorescence detection. The concentrations ranged between 0.001 ± 0.001 mg·kg−1, on a baby wipe, and 300.480 ± 8.819 mg·kg−1, on glycerin soap, which may correspond to an estimated daily dermal exposure of 277.10 ± 0.02 µg·day−1 on the population of Oporto children. This value is in the range of the results observed for adults, although no information of toxicological risk for children is available.